Factors Affecting The Cost Gap Between INA CBGs Tariff and Hospital Tariff for Patients with Dengue Hemorrhagic Fever in Ngawi Regional Public Hospital, East Java - Ariwardani, Betty Nurizky; Tamtomo, Didik Gunawan; Murti, Bhisma (Journal of Health Policy and Management, 2019)
Background: Dengue Hemorrhagic Fever (DHF) has a high cost burden. Payment for hospital treatment was paid by Health insurance (BPJS) with a case based payment method in the era of the National Health Insurance. This method allowed the hospital to gain profit or loss. This study aimed to analyze the factors that influence the differences in Indonesian Cased Based Groups (INA CBGs) with the medical service costs for DHF in dr. Soeroto hospitals, Ngawi Regency.Subjects and Method: This study used an observational analytic study with a cross-sectional approach conducted at dr. Soeroto Hospital, Ngawi Regency, East Java in September - October 2019. A sample of 200 subjects was selected by using simple random sampling. The dependent variable was the difference in rate. The independent variables were class of care, length of stay, age, blood transfusion, comorbidity and complications. Data analysis was using multiple linear regression with Stata 13.Results: INA CBG rates (mean= Rp 6,120,000; SD= Rp 2,330,000) was lower than the cost of hospital treatment (mean= Rp 7,070,000; SD= Rp 4,650,000). There is a negative relationship between the difference in rates and it was statistically significant on the length of stay (b= 0.73; Cl 95%= -1,131,915 to -329,501; p= <0.001), patients? age (b= 0.41; Cl 95%= -707,099 to -110,293; p= 0.008), blood transfusion action (b= 0.79; Cl 95%= -1,549,446 to -34,190; p= 0.041), and comorbidity (b= 1.14 ; Cl 95%= -1,817,112 to -474,641; p= 0.001). While there was a statistically insignificant relationship between classes of care (b= 0.42; Cl 95% = -931,443 to 82,607; p= 0.100) and complication (b= 0.34; Cl 95%= -1,093,208 to 408,223; p= 0.369).Conclusion: Difference in INA CBG rates and hospital medical service costs were affected by the class of care, length of stay, age, blood transfusion, comorbidity and complications.Keywords: INA-CBG?s rates, hospital rates, care cost, dengue hemorrhagic fever.Correspondence: Betty Nurizky Ariwardani. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta, Central Java, Indonesia. Email: bettyna175@gmail.com. Mobile: 082233243164.Journal of Health Policy and Management (2019), 4(3): 204-213https://doi.org/10.26911/thejhpm.2019.04.03.08